Analysis of microbial communities in wheat, alfalfa, and oat crops after Tilletia laevis Kühn infection - Shen, Yuyang; Delai, Chen; Liu, Taiguo; Chen, Wanquan; Li, Guangkuo; Gao, Haifeng; Gao, Li (Frontiers in Microbiology, 2024)
Common bunt caused by Tilletia laevis Kühn is one of the most serious fungal disease of wheat. The root-microbial associations play key roles to protect plants against biotic and abiotic factors. Managing these associations offer a platform for improving the sustainability and efficiency of agriculture production. Here, by using high throughput sequencing, we aimed to identify bacterial and fungal association in wheat, alfalfa and oat crops cultivated in different years in Gansu province of China.Soil samples (0-6 cm below the surface) from infected wheat by T. laevis had significantly more bacterial and fungal richness than control samples according to chao1 analysis. We found some dominant fungi and bacterial phyla in infected wheat by T. laevis, such as Proteobacteria, Acidobacteria, Actinobacteria, Chloroflexi, Ascomycota, Basidiomycota and Mortierellomycota. We also analysed chemical and enzymatic properties of soil sample after T. laevis inoculation. The total nitrogen, total kalium, ammonium nitrogen, available kalium, organic carbon, invertase, phosphatase and catalase were more in T. laevis infected samples compared to control samples, while pH, total phosphorus, nitrate nitrogen, available phosphorus and urease were more in control samples compared to T. laevis infected samples. The results of this study will contribute to the control of wheat common bunt by candidate Antagonistic microorganisms and adverse properties of soil.